2013
DOI: 10.1016/j.jgo.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on treatment trends and clinical outcome in patients with metastatic renal cell carcinoma

Abstract: OBJECTIVES Clinical outcomes in older adults with metastatic renal cell carcinoma (mRCC) are poorly understood, particularly in the era of targeted therapies. We characterize survival and relevant treatment-related variables in a modern series. MATERIALS AND METHODS From an institutional database including 562 patients with RCC, a total of 219 patients with metastatic disease were identified for the current analysis. Survival was assessed in four age-based cohorts: (1) age < 55, (2) age 55–64, (3) age 65–74,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In our aforementioned institutional experience, we observed that 70% of patients aged ≥ 75 years did not receive systemic therapy. 5 In contrast, only 33.5% of patients aged < 75 years received no systemic therapy. The reasons for this are unclear; our analyses were limited by a lack of comorbidity data, and it is entirely possible that the older adults in our series were less able to withstand systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our aforementioned institutional experience, we observed that 70% of patients aged ≥ 75 years did not receive systemic therapy. 5 In contrast, only 33.5% of patients aged < 75 years received no systemic therapy. The reasons for this are unclear; our analyses were limited by a lack of comorbidity data, and it is entirely possible that the older adults in our series were less able to withstand systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To explore a more heterogeneous pool, we performed an assessment of our institutional database, capturing outcomes associated with 219 patients with mRCC (irrespective of therapeutic assignment). 5 Survival was significantly shorter in those patients aged ≥ 75 years (12.5 vs. 26.4 months; P = .003).…”
Section: Introductionmentioning
confidence: 92%
“…Age is also likely to influence treatment decisions, in addition to concerns over toxicity and underlying tumour biology. While the selection of first‐line treatment, the use of an initial watchful‐waiting approach, and the impact of age on treatment decisions have been explored by some studies, these are yet to be examined in an Australian population, where the limited number of Pharmaceutical Benefits Scheme‐reimbursed treatment options are likely to have a significant impact .…”
Section: Introductionmentioning
confidence: 99%
“…Prior clinical and experimental studies provided multiple indications as to the role of ageing in cancer biology and progression (Ershler, Socinski, and Greene 1983;Ershler et al 1984;Pili, Guo, Chang, Nakanishi, Martin, and Passaniti 1994;Rivard, Fabre Ageing is presently seen merely as a source of additional side effects and limitations in the context of antiangiogenic therapeutics, and the clinical activity of VEGF inhibitors is thought to be retained in both younger and older patients (Pal, Hsu, Hsu, Hu, Bergerot, Carmichael, Saikia, Liu, Lau, Twardowski, Figlin, and Yuh 2013;Escudier, Albiges, and Sonpavde 2013;Killock2014). This is enforced by comparable clinical efficacy of these drugs at the late age cutoff, typical for major indications such as in mccRCC patients (Killock2014).…”
Section: Discussionmentioning
confidence: 99%
“…While functionality of the VEGF pathway changes markedly with age (Rivard, Fabre, Silver, Chen, Murohara, Kearney, Magner, Asahara, and Isner 1999), systematic studies in this regard involving sunitinib effects are largely lacking. Moreover, the efficacy of this agent is predominantly compared between older groups of cancer patients (Chowdhury et al 2013;Pal et al 2013;Killock2014), while the biological effects in more distant age groups (elderly and children) are scarcely characterized.…”
Section: Introductionmentioning
confidence: 99%